Expectation management of policy leaders: Evidence from COVID-19 - Peter Haan; Andreas Peichl; Annekatrin Schrenker; Georg Weizsäcker; Joachim Winter (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
This paper studies how the communication of political leaders affects the expectation formation of the public. Specifically, we examine the expectation management of the German government regarding COVID-19-related regulatory measures during the early phase of the pandemic. We elicit beliefs about the duration of these restrictions via a high-frequency survey of individuals, accompanied by an additional survey of firms. To quantify the success of policy communication, we use a regression discontinuity design and study how beliefs about the duration of the regulatory measures changed in response to three nationally televised press conferences by Chancellor Angela Merkel and the Prime Ministers of the German federal states. We find that the announcements of Angela Merkel and her colleagues significantly prolonged the expected duration of restrictions, with effects being strongest for individuals with higher ex-ante optimism.
Keywords: D12; D84; H12; 330; Expectations; Belief updating; COVID-19; Shutdown